Clinical outcomes of epidural and intradural decompression for treatment of degenerative cervical myelopathy. Issue 6 (June 2020) - Jiao, Genlong; Li, Zhizhong; Zhou, Pan; Yang, Jinpei; Li, Xueshi
Objective: This study was performed to examine the clinical outcomes of epidural and intradural decompression for degenerative cervical myelopathy. Methods: The data for 13 patients who underwent epidural and intradural decompression for treatment of degenerative cervical myelopathy (study group) and 20 patients who underwent only cervical laminoplasty, fusion, and epidural decompression (historical control group) were retrospectively reviewed. The preoperative and postoperative neurological status was evaluated using the Japanese Orthopaedic Association (JOA) score. Results: All patients' neurological symptoms were significantly improved at the final follow-up. In the study group, the patients' mean preoperative JOA score was 8.07 ± 1.80, and the final score improved by 70.88% ± 21.18%. The blood loss and operation time were significantly greater in the study group than control group. The recovery time was shorter in the study group than control group. The improvement rate was not significantly different between the two groups. Conclusions: A pia mater incision with separation of the arachnoid adhesion can significantly improve the cerebrospinal fluid flow and spinal blood flow in degenerative cervical myelopathy. Arachnoid adhesion can lead to intradural spinal scar compression. The surgical intervention described herein can achieve satisfactory neurological outcomes and shorten the recovery time.